2022
DOI: 10.1111/btp.13139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human disturbance on the abundance of non‐breeding shorebirds in a subtropical wetland

Abstract: Shorebird populations have declined due to several threats throughout their annual cycle. Anthropogenic disturbance is one of the most ubiquitous threats to shorebird conservation in North America. Here, we studied the influence of human disturbance on shorebird community dynamics during migration and winter in Ensenada de La Paz, a subtropical coastal wetland in Mexico. We used negative binomial generalized linear mixed models to investigate the associations between spatial, biological, and anthropogenic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Surprisingly, with the exception of wetlands in Brazil, we did not find evidence that the proximity of a given site to urban areas had a significant effect on either shorebird presence or abundance (Tables 2 & 3). We had predicted that a close proximity to cities would have a negative effect on both presence and abundance, especially for shorebirds using beach habitats, as several studies have previously indicated that proximity to humans affects shorebirds during the breeding (Liley and Sutherland 2007, Hevia et al 2023), migratory (Pfister et al 1992, Murchison et al 2016), and nonbreeding seasons (LeDee et al 2008, Palacios et al 2022, Swift et al 2023). However, most cities are located close to estuaries (Small and Nicholls 2003) and, thus, the reliance of shorebirds on estuarine habitats may be stronger than the pressure to avoid urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, with the exception of wetlands in Brazil, we did not find evidence that the proximity of a given site to urban areas had a significant effect on either shorebird presence or abundance (Tables 2 & 3). We had predicted that a close proximity to cities would have a negative effect on both presence and abundance, especially for shorebirds using beach habitats, as several studies have previously indicated that proximity to humans affects shorebirds during the breeding (Liley and Sutherland 2007, Hevia et al 2023), migratory (Pfister et al 1992, Murchison et al 2016), and nonbreeding seasons (LeDee et al 2008, Palacios et al 2022, Swift et al 2023). However, most cities are located close to estuaries (Small and Nicholls 2003) and, thus, the reliance of shorebirds on estuarine habitats may be stronger than the pressure to avoid urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, human disturbance or declining habitat quality could occur at sites even in the face of conservation outcomes (e.g., protected area designation). If a critical driver of site‐specific shorebird decline (e.g., human disturbance; Palacios et al., 2022) is not being mitigated with the activities being supported by investments, the lack of a difference in trends compared with sites with no conservation investment is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…We logged each nest using a GPS. During each visit and each transect, we quantified the potential threats in the areas, including the number of people encountered (pedestrians, fishermen, and beach-and-sun tourists), vehicles (cars, tractors, and motorbikes), and dogs (free-ranging or with owners but off-the-leash), as done by Palacios et al (2022).…”
Section: Study Areamentioning
confidence: 99%
“…Shorebirds are a group of species that are highly dependent on coastal environments. In the case of shorebirds, human-related disturbances can affect individuals’ breeding, roosting, and foraging activities (Palacios et al 2022). Pedestrians, dogs, and motorized vehicle traffic on beaches also affect the energetic expenditure of shorebirds (Navedo et al 2019; Cortés et al 2021; Oliveros et al 2021; Gómez-Serrano 2021).…”
Section: Introductionmentioning
confidence: 99%